The Implementation of Islam Wasathiyah Thought in Dayah Darul Hikmah Islamiyah, West Aceh - Ummi Habibatul Islamiyah (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The contribution of Islamic boarding schools is quite immense to the Indonesian nation, but there are still many parties who doubt the implementation of the Islamic teachings of Wasathiyah in Islamic boarding schools and even suspect the doctrine of radicalism has grown and developed in Islamic boarding schools. This article discusses the implementation of Islam Wasathiyah values at the Dayah Darul Hikmah Islamiyah in West Aceh, along with solutions so that the doctrine of radicalism does not spread more widely. This type of research is qualitative. The author collects data through literature study, observation, and interviews. The findings of this study are the process of applying the values of Islam Wasathiyah teachings at the Dayah Darul Hikmah Islamiyah through the curriculum, grounding the Islamic teachings of Wasathiyah, providing advice and discipline/firm in enforcing the Dayah rules. The solution so that radicalism does not spread is by implementing the Aswaja curriculum, fostering deviant institutions, increasing da'wah in the media, filtering negative content in the media, and strengthening Islam Wasathiyah literacy & the dangers of radicalism.